Dialectical Method and the Critical Political Economy of Culture - Brice Nixon (tripleC: Communication, Capitalism & Critique)
This article argues that the quality that defines critical political economy is its critical method. Definitions of the critical political economy of culture are considered and shown to focus on specific theoretical concerns while not fully addressing the fundamental issue of method. Method is here discussed in terms of the way human reason is used to produce knowledge. A critical method for Marx is a historical materialist dialectical method, thus this paper argues for a deeper consideration of the Marxist dialectical method in relation to critical political-economic theorizing. Sources for methodological consideration from Marx to 20th-century Western Marxists are outlined. The potential contribution of the Marxist dialectical method in the continued development of the critical political economy of culture is demonstrated by showing the possibility of developing a complementary critical political economy of consciousness. Smythe’s theorizing of audiences as workers is considered as a useful starting point, and its potential development through incorporation of the work of other critical scholars of media and culture is outlined.